In Terram Visionis - Makarov, Dmitry I. (Scrinium, 2017)
In his Transfiguration homily (ca. 1315) Nicephorus Choumnus, a pre-Palamite thinker, put forward a theory that Abraham at the oak of Mamre was granted the vision of the Trinity. This is the third type of the exegesis of Genesis 18, according to Lars Thunberg. By comparison with: (a) Gregory of Nyssa and other patristic authors; (b) the early second-century Testament of Abraham (TA) we have put forward a hypothesis that Abraham, in Choumnus’ view, was granted the vision of the divine light and glory, most likely, in the form of a bright cloud very similar to that which later overshadowed the elected of the prophets and the Apostles on Mount Tabor. Thus, Nicephorus Choumnus mentioned Abraham together with such symbolic OT figures, as Moses and Elijah, who had also the honor of seeing the Face of God on Tabor.